The Effect of Profitability, Leverage, and Firm Size on Tax Avoidance (Evidence from the Indonesian Agriculture Sector) - Junaidi, Hendry; Yunita, Khristina (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of profitability, leverage, and firm size on tax avoidance in agricultural-sector companies listed on the Indonesia Stock Exchange during the 2019–2021 period. The study employs a quantitative approach using secondary data obtained from corporate financial statements. The sample was selected through purposive sampling and consisted of 43 firm-year observations. Tax avoidance was measured using the Effective Tax Rate, profitability was measured using Return on Assets, leverage was measured using the Debt-to-Equity Ratio, and firm size was measured using the natural logarithm of total assets. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 27. The results show that profitability has a negative and significant effect on the Effective Tax Rate, indicating that higher profitability is associated with greater tax avoidance. Leverage and firm size have no significant effects on tax avoidance. Simultaneously, profitability, leverage, and firm size significantly affect tax avoidance. The coefficient of determination is 58.2%, indicating that the research model explains 58.2% of the variation in tax avoidance.